The relationship between leadership empowering behaviour, ethical leadership, and employees’ psychological empowerment with turnover intention at XYZ Malaysia Sdn. Bhd. / Ainaa Farhanah Saiful Azhan, Nur Aqilah Mohammad Khairri and Nur Atiqah Muzaffar - Saiful Azhan, Ainaa Farhanah; Mohammad Khairri, Nur Aqilah; Muzaffar, Nur Atiqah (2019)
Employees are organization's most important and valuable assets. The success of an organization could not be achieved without the support and contribution of employees. This main objective of the study is to determine the relationship between leadership empowering behaviour, ethical leadership and employees’ psychological empowerment with turnover intention at XYZ Malaysia Sdn. Bhd. XYZ Malaysia Sdn. Bhd. was chosen because the company has a high number of turnover rate for the past two years. The dependent variable is turnover intention and independent variables are identified as leadership empowering behaviour, ethical leadership and employees’ psychological empowerment. One hundred sets of questionnaire were distributed to the lower level employees of XYZ Malaysia Sdn. Bhd. The result showed that all of the independent variables were significantly related to dependent variable. There were significant negative correlations between leadership empowering behaviour, ethical leadership and employees’ psychological empowerment with turnover intention. It was found that leadership empowering behavior was the most dominant variable in affecting turnover intention at XYZ Malaysia Sdn. Bhd. In conclusion, the higher the leadership empowering behavior, ethical leadership and employees’ psychological empowerment, the lower the turnover intention at XYZ Malaysia Sdn. Bhd. There were few suggested strategies in retaining the employees, which focused on recognition, training and development, and exit interview. Consequently, this research has shown that it provides valid and reliable information for future researchers.